PERBANDINGAN KADAR HEMOGLOBIN IBU HAMIL MENGGUNAKAN ALAT HEMOCHROMA PLUS METODE POCT DENGAN ALAT HEMATOLOGI SEMI OTOMATIK: THE DIFFERENCE IN HEMOGLOBIN LEVELS IN PREGNANT WOMEN USING THE HEMOCHROMA PLUS POCT METHOD WITH A SEMI-AUTOMATIC HEMATOLOGY DEVICE - Malihah, Malihah; Sundari, Titik; Yusmiati, Siti Nur Husnul (Jurnal SainHealth, 2025)
Anemia is a condition where hemoglobin levels, hematocrit and red blood cell counts decrease below normal values. This research aims to find out. A simple examination of hemoglobin levels using an HB Meter with a Hemachroma Plus Tool, the POCT method, has the advantage of only requiring a small amount of capillary blood sample. Research title "Comparison of Hemoglobin Levels of Pregnant Women Using the Hemochroma Plus POCT Method and Semi- Automatic Hematology Equipment in the Lenteng Community Health Center Laboratory, Sumenep Regency." Number of Research Subjects: 50 ANC pregnant women. Capillary blood examination material for POCT devices and K3EDTA venous blood for semi-automatic hematology devices. Data processing used the Independent T Test and the results obtained were p=0.001 (?>0.05), there was a higher difference in hemoglobin levels on the POCT tool compared to the semi- automatic hematology tool. The average value of the POCT Hb level is (12.18) or 12.2 G/dL and the hematology analyzer tool's average value of the HB level is 11.29 or 11.3 G/dL. Conclusion: The HB level value of the POCT tool is higher 8% compared to semi-automatic hematology equipment